Vague retellings of personal narratives in temporal lobe epilepsy. (April 2023) - D'Aprano, Fiore; Malpas, Charles B.; Roberts, Stefanie; Saling, Michael M.
Highlights: A multi-level discourse analysis examined language in temporal lobe epilepsy (TLE). When retelling personal memories, disturbed fluency, cohesion, and coherence emerges. Over repetitions they consistently produce a vague account. This possibly relates to the neurolinguistic demands of recalling personal events. Abstract: Purpose: Aside from deficits identified in single-word level retrieval, individuals with temporal lobe epilepsy (TLE) exhibit clinical oddities, such as circumstantiality in their language production. Circumstantiality refers to the use of language which is pedantic, repetitive, and overly detailed. This becomes particularly evident when elicitation tasks impose minimal structure, or when impersonal narratives are retold over consecutive occasions. Personal reminiscence is highly specific and localised in time, placing unique demands on cognitive-linguistic systems. It is hypothesised that the nature of this elicitation paradigm will produce a unique psycholinguistic phenotype in those with TLE. Among controls there is a compression of output for impersonal narratives, meaning that they use fewer words over less time and are more fluent. The opposite effect is observed when personal narratives are retold. Methods: To investigate the micro- and macrolinguistic processes underpinning personal discourse production in TLE, we examined the elicited language output of 15 surgically naïve individuals with TLE and 14 healthy controls. Participants were asked to recall and re-tell an autobiographical memory on four immediately consecutive occasions, representing an alternative unstructured elicitation. Following transcription and coding of output, a detailed multi-level discourse analysis of output volume, fluency, cohesion, and coherence was conducted. Results: As anticipated, a distinctly different pattern emerged in TLE when compared with controls who did not compress their output volume across repetitions but instead produced greater novelty, and a more coherent and refined account over time. Individuals with TLE consistently told a less distinct story across repetitions, with disturbances in fluency, cohesion, and coherence. Conclusion: This reflects a reduced capacity to produce a coherent mental representation, in all likelihood related to the neurolinguistic demands of recalling and retelling specific personal events.